Preparation of Ag/Cu/Ti Nanofluids by Spark Discharge System and Its Control Parameters Study - Kuo-Hsiung Tseng; Juei-Long Chiu; Heng-Lin Lee; Chih-Yu Liao; Hong-Shiou Lin; Yi-Syuan Kao (Advances in Materials Science and Engineering)
This study selected silver, copper, and titanium as the research objects to explore the relationship between nanofluids properties and electrical discharge machining (EDM) processes. Regarding the products, UV-visible spectroscopy (UV-Vis) was applied to measure the concentration distribution of nanofluids; zeta-size analysis is applied for measuring nanometal particles’ Zeta-Potential and the size distribution of metallic particles in the fluid. Finally, various instruments, including scanning electron microscope (SEM), were applied to observe the shape, size, and composition ratio of metal particles after processing. According to the experimental results, the control of the discharge pulse time, in addition to affecting the concentration of metallic liquid and temperature in the process, affects the size of the metal particles after the process. As the resistivity of silver and copper is very low, at about 15×10-9 Ω·m, if TON is set to between 10~50 μs, good preparation efficiency can be obtained. The resistivity of titanium is 420×10-9 Ω·m, which is much larger than that of silver or copper. Hence, TON should be set to approximately 100 μs to achieve a good discharge success rate.